Advancements in Bicomplex and Tricomplex Numbers: A Historical and Analytical Perspective - Wagh, Mamta Amol (Exploration of Knowledge and Information in Sciences, Edition 1, 2025)
In this chapter, an introduction to bicomplex numbers was provided which may be helpful to any student interested in knowing about them. Further, tricomplex numbers have been defined and their seven different representations are given. These representations may be helpful in analyzing the space with different perspectives. Some of the recent studies in bicomplex analysis have also been summarized. The mathematical concept of bicomplex numbers has been applied to quantum mechanics, signal processing, electromagnetics, and other fields by various mathematicians. Our study and different representations could be valuable in understanding and analyzing recent developments in this area.